Survival of Surfactant Protein-A1 and SP-A2 Transgenic Mice After Klebsiella pneumoniae Infection, Exhibits Sex-, Gene-, and Variant Specific Differences; Treatment With Surfactant Protein Improves Survival - Thorenoor, Nithyananda; Umstead, Todd M.; Zhang, Xuesheng; Phelps, David S.; Floros, Joanna (Frontiers in Immunology, 2018)
Surfactant protein A (SP-A) is involved in lung innate host defense and surfactant-related functions. The human SFTPA1 and SFTPA2 genes encode SP-A1 and SP-2 proteins, each gene has been identified with numerous genetic variants. SP-A1 and SP-A2 differentially enhance bacterial phagocytosis. Sex differences have been observed in pulmonary disease and in survival of wild type and SP-A knockout (KO) mice. The impact of human SP-A variants on survival after infection is unknown. In this study, we determined whether SP-A variants differentially affect survival of male and female mice infected with Klebsiella pneumoniae. Transgenic (TG) mice, carrying a different human (h) SP-A1 (6A2, 6A4), SP-A2 (1A0, 1A3) variant or both variants SP-A1/SP-A2 (6A2/1A0, co-ex), and SP-A- KO, were utilized. The hTG and KO mice were infected intratracheally with K. pneumoniae bacteria, and groups of KO mice were treated with SP-A1 or SP-A2 either prior to and/or at the time of infection and survival for both groups was monitored over 14 days. The binding of purified SP-A1 and SP-A2 proteins to phagocytic and non-phagocytic cells and expression of cell surface proteins in alveolar macrophages (AM) from SP-A1 and SP-A2 mice was examined. We observed gene-, variant-, and sex-specific (except for co-ex) differences with females showing better survival: a) Gene-specific differences: co-ex = SP-A2 > SP-A1 > KO (both sexes); b) Variant-specific survival co-ex (6A2/1A0) = 1A0 > 1A3 = 6A2 > 6A4 (both sexes); c) KO mice treated with SPs (SP-A1 or SP-A2) proteins exhibit significantly (p < 0.05) better survival; d) SP-A1 and SP-A2 differentially bind to phagocytic, but not to non-phagocytic cells, and AM from SP-A1 and SP-A2 hTG mice exhibit differential expression of cell surface proteins. Our results indicate that sex and SP-A genetics differentially affect survival after infection and that exogenous SP-A1/SP-A2 treatment significantly improves survival. We postulate that the differential SP-A1/SP-A2 binding to the phagocytic cells and the differential expression of cell surface proteins that bind SP-A by AM from SP-A1 and SP-A2 mice play a role in this process. These findings provide insight into the importance of sex and innate immunity genetics in survival following infection.